1999
DOI: 10.2337/diabetes.48.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Surgical removal of visceral fat reverses hepatic insulin resistance.

Abstract: We directly examined whether visceral fat (VF) modulates hepatic insulin action by randomizing moderately obese (body wt approximately 400 g) Sprague-Dawley rats to either surgical removal of epididymal and perinephric fat pads (VF-; n = 9) or a sham operation (VF+; n = 11). Three weeks later, total VF was fourfold increased (8.5 +/- 1.2 vs. 2.1 +/- 0.3 g, P < 0.001) in the VF+ compared with the VF- group, but whole-body fat mass (determined using 3H2O) was not significantly different. The rates of insulin inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
242
4
14

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(273 citation statements)
references
References 15 publications
12
242
4
14
Order By: Relevance
“…The first notion is supported by findings that intra-abdominal fat mass reduction improves insulin sensitivity in rats [4], whereas implantation of cultured adipocytes into the peritoneal cavity of mice induces insulin resistance [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The first notion is supported by findings that intra-abdominal fat mass reduction improves insulin sensitivity in rats [4], whereas implantation of cultured adipocytes into the peritoneal cavity of mice induces insulin resistance [11].…”
Section: Discussionmentioning
confidence: 96%
“…elderly people or patients with certain forms of lipodystrophy) are prone to develop insulin resistance [1,2]. Second, removal of intra-abdominal fat improved insulin sensitivity [3,4], whereas the removal of subcutaneous fat tissue by liposuction in obese humans did not improve insulin action [5]. Thus, the pattern of body fat distribution, especially abdominal fat accumulation, determines insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal of visceral fat from laboratory rodents has been shown to improve metabolic function, including insulin sensitivity (Barzilai et al ., 1999). Furthermore, reduction of visceral fat by omentectomy produced significant positive and long‐term effects on glucose homeostasis in humans (Thorne et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…65 A recent study reported that surgical removal of visceral fat reverses hepatic insulin resistance. 66 …”
Section: The Association Of Nash With Obesitymentioning
confidence: 99%